Development of plasmonic sensor using gold nanobipyramids for detection of glyphosate based pesticide - Nafisah, Suratun (2020)
The development of plasmonic sensor using gold nanobipyramids (GNBPs) as sensing material for detection of glyphosate based pesticide (GBP) has been performed. The GNBPs was synthesised using seed-mediated growth method (SMGM). In the synthesis process, the effect of three different additive acid types which are chloric, sulfuric, and fluoric acid, and its concentration in growth solution were investigated to obtain optimum surface density and aspect ratio of GNBPs. The structure obtained is gold with face-centered cubic (FCC) crystal structure and diffraction peaks at 2θ values of 38.2º and 44.5º, which corresponding to (111) and (200) planes, respectively. The GNBPs have surface density from 5.21±0.44 to 91.46±3.32% and aspect ratio from 2.00±0.02 to 2.76±0.05. It exhibits two resonance peaks at wavelength around 550 and 580 nm, corresponding to transverse surface plasmon resonance (t-SPR) and at wavelength around 720 and 780 nm, corresponding to longitudinal surface plasmon resonance (l-SPR). In sensing study, the changes in the peak position and intensity for both t-SPR and l-SPR, respectively, in de-ionized water (DIW) as reference and glyphosate solutions as target analyte were measured. The presence of glyphosate as low as 1 mg/mL was successfully detected using this sensor. Besides, gold bone nanorods (GBNRs) and gold nanorods (GNRs) have been employed as sensing material and the results show the GNBPsbased plasmonic sensor demonstrate improved sensitivity compared to other sensors. For t-SPR band, the GNBPs provided sensitivity factor as high as 4.76 and 5.17 times larger than the sensitivity factor of GBNRs and GNRs, while for l-SPR band, the sensitivity factor of GNBPs are 2.87 times larger than GBNRs and 1.57 times larger than GNRs. Also, the selectivity of GNBPs-based plasmonic sensor towards glyphosate is higher than its response to four different analytes, ie. chlorpyrifos, acetic acid and acetone. As a conclusion, the additive acid types and concentrations influenced the morphological of GNBPs and the implementation as a sensing vi material in plasmonic sensor has been proven improved the sensitivity and has good selectivity towards glyphosate.